Maturity degree of composts from municipal solid wastes evaluated by differential scanning calorimetry - De Oliveira, S. C. [UNESP]; Provenzano, M. R.; Santiago Silva, M. R. [UNESP]; Senesi, N. (Taylor & Francis, 2002)
Differential scanning calorimetry (DSC) in association with chemical analysis was applied to assess the maturity reached by the organic fraction of Municipal Solid Wastes (MSW) subjected to composting processes with manual and fixed aeration and sampled at different composting times. Thermograms showed that the difference in the treatments, i.e., the manual aeration and the fixed aeration, had no relevant effect on the stabilization and maturation of OM in the substrates. Common thermal effects observed were: a low temperature endotherm assigned to dehydration and/or loss of peripheral polysaccharides chains; a medium temperature exotherm assigned to loss of peptidic structures, and a high temperature exotherm assigned to oxydation and polycondensation of aromatic nuclei of the molecule. Results obtained suggest that in the experimental conditions used, a shorter time of composting (about 30 d) appears adequate, in order to limit the extended mineralization of OM, whereas a prolonged composting time (up to 132 d) would produce a compost of poor quality with high ash content and low OM content.
Keywords: Compost; Differential scanning calorimetry; Maturity degree; Organic matter; organic matter; peptide; polysaccharide; calorimetry; compost; municipal solid waste; aeration; ash; chemical analysis; chemical parameters; chemical reaction; composting; concentration (parameters); controlled study; dehydration; differential scanning calorimetry; intermethod comparison; mineralization; oxidation; polymerization; solid waste management; temperature sensitivity; thermography; time; Biodegradation, Environmental; Calorimetry, Differential Scanning; Humic Substances; Models, Theoretical; Oxygen; Refuse Disposal; Temperature; Fraxinus